Awareness and knowledge of pneumococcal vaccination in cardiology outpatient clinics and impact of physicians' recommendation on vaccination rates. (11th May 2022) - Ekin, T; Kis, M; Gungoren, F; Atici, A; Kunak, AÜ; Mutlu, D; Katkat, F; Demir, M; Sarac, İ; Soydan, E; Karaduman, M; Bekar, L; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Although there is not enough data on pneumococcal vaccination status in patients with cardiovascular disease and or risk factors in our country, it is known that vaccination rates are quite low in the current data. Purpose: We aimed to evaluate the awareness of pneumococcal vaccination (PCV13, PPSV23) in general cardiology outpatient clinics and impact of physician's recommendation (with educational brochures) on vaccination rate. Methods: Awareness of vaccination, before COVID-19 pandemic, was measured in patients admitting to cardiology outpatient clinics from 40 center of our country by a questionnaire contained 19 questions. The demographics (including gender, age, educational level, awareness vaccination level) and comorbidities were obtained. The vaccination rates were calculated within 3-months follow-up from the admitting of patient to cardiology clinics. Results: The 403 (18.2%) of patients with previous pneumococcal vaccination were excluded from the study. The mean age of study population (n=1808) was 61.9±12.1 years and 55.4% were male. The 58.7% had coronary artery disease, hypertension (74.1%) was the most common risk factor and 32.7% of the patients had never been vaccinated although they had information about vaccination before. The 98.5% were referred to family medicine (n=1412, 78.1%) or vaccination outpatient clinics (n=370, 20.5%) and the vaccination rate was 62.1% during the follow-up period. The differences between vaccinated and not-vaccinated patients are presented in Table 1. The physician's recommendation was positively correlated with vaccination intention and behavior in our participants. Multivariate logistic regression analysis showed a significant between vaccination and female sex [OR=1.55 (95% CI=1.25–1.92), p<0.001], higher education level [OR=1.49 (95% CI=1.15-1.92), p=0.002] patients' knowledge [OR=1.93 (95% CI=1.56-2.40), p<0.001], and their physician's recommendation [OR=5.12 (95% CI=1.92-13.68), p=0.001]. Conclusion: To our knowledge this is the first report about the awareness pneumococcal vaccination rates and impact of physician's recommendation in patients with cardiovascular disease by high study population. These findings suggest providing information on the benefits of vaccination by physician's and educational advice was significantly associated with an increase vaccination rate and have a key role.